Oral health conditions of geriatrics - Ngwu, Chika Charity; Fadare, Stephen Ayoade (Orapuh Journal, 2023)
Oral health is a part of general health, but maintaining good oral health is a bit awkward and different in geriatrics. The dental care of geriatric patients is challenging and needs more attention than the dental care of younger people. Aging is a natural process associated with many oral diseases and problems. A healthy mouth that will last well into old age is crucial for a healthy body. This review aimed to keep clinicians informed on the oral health status of senior citizens, as well as the obstacles they face because of systemic disorders and changes in their oral tissues as they age. The authors reviewed previously published articles in journals and provided up-to-date knowledge on the common oral health concerns of the elderly. The authors conducted a narrative evaluation of geriatric oral health issues. The writing process took three months, (between November 2021 and January 20, 2022). We searched databases such as PubMed, Z-library, Publon, Medline, JSTOR, and Google Scholar, and obtained original articles published in various journals, textbooks, and review papers. Conclusively, good oral health helps one to stay healthy, maintain quality of life, and preserve independence. Good oral hygiene, adequate nutrition, and regular visits to the dentist will help protect one’s teeth for a lifetime. This review demonstrated that many geriatrics encounter oral health problems and need serious attention to assuage their oral health conditions.